Cape Fear [videorecording (DVD)] - Bernstein, Elmer (Universal Studios Home Entertainment, 2005)
Fourteen years after being imprisoned, vicious psychopath Max Cady (Robert De Niro) emerges with a single-minded mission: to seek revenge on his attorney Sam Bowden (Nick Nolte).